Pengaruh Kualitas Pelayanan, Persepsi Harga Dan Promosi Terhadap Kepuasan Pelanggan Di Kepu Barbershop Malang - Al Aden, Zait Islach; Basalamah, Muhammad Ridwan; Wahono, Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
AbstractÂ This study aims to analyze the simultaneous influence of service quality, price perceptions, and promotions on customer satisfaction at Kepu Barbershop Malang, involving a sample of 85 respondents. Using SPSS Version 16 for data analysis, the study applied quantitative methods and various tests, including validity, reliability, and multiple linear regression. The results indicate that while service quality and price perceptions do not significantly affect customer satisfaction individually, promotions have a notable impact on customer satisfaction at the barbershop.Â Keywords: Service Quality, Perceived Price and Promotion on Customer Satisfaction in Kepu Barbeshp Malang